Exploiting fandom : how the media industry seeks to manipulate fans - Stanfill, Mel, 1983- (University of Iowa Press, 2019)
As more and more fans rush online to share their thoughts on their favorite shows or video games, they might feel like the process of providing feedback is empowering. However, as fan studies scholar Mel Stanfill argues, these industry invitations for fan participation indicate not greater fan power but rather greater fan usefulness. Stanfill's argument, controversial to some in the field, compares the "domestication of fandom" to the domestication of livestock, contending that, just as livestock are bred bigger and more docile as they are domesticated, so, too, are fans as the entertainment industry seeks to cultivate a fan base that is both more useful and more controllable. By bringing industry studies and fan studies into the conversation, Stanfill looks closely at just who exactly the industry considers "proper fans" in terms of race, gender, age, and sexuality, and interrogates how digital media have influenced consumption, ultimately finding that the invitation to participate is really an incitement to consume in circumscribed, industry-useful ways.